An Update on the Current Management of Sigmoid Volvulus - Kumar H.R (Achievements and Challenges of Medicine and Medical Science Vol. 6, 2024)
Sigmoid volvulus is a common cause of large bowel obstruction in older patients in the West and in younger patients in the East. The diagnosis is made by clinical examination, blood investigations and imaging modalities like X-ray and computerized tomography. Sigmoid volvulus can be divided into a complicated or uncomplicated clinical presentation. For uncomplicated sigmoid volvulus, the treatment is initially endoscopic decompression and flatus tube insertion, and this is followed by an elective sigmoid resection. For complicated sigmoid volvulus, surgical resection is the treatment of choice and Hartmann’s procedure is the most common operation as anastomosis is rarely performed. We have conducted this review article to review the current management of sigmoid volvulus.